Genetic polymorphism in Methylenetetrahydrofolate Reductase chloride transport protein 6 (MTHFR CLCN6) gene is associated with keratinocyte skin cancer in a cohort of renal transplant recipients. Issue 2 (2nd February 2022) - Griffin, L.; Ho, L.; Akhurst, R. J.; Arron, S. T.; Boggs, J. M. E.; Conlon, P.; O'Kelly, P.; Toland, A. E.; Epstein, E. H.; Balmain, A.; Bastian, B. C.; Moloney, F. J.; et al.
Abstract: Background: Renal transplant recipients (RTRs) are at increased risk of keratinocyte cancer (KC), especially cutaneous squamous cell carcinoma (cSCC). Previous studies identified a genetic variant of the Methylenetetrahydrofolate Reductase ( MTHFR ) gene, C677T, which conferred a risk for diagnosis of cSCC in Irish RTRs. Objective: We sought to find further genetic variation in MTHFR and overlap genes that may be associated with a diagnosis of KC in RTRs. Methods: Genotyping of a combined RTR population ( n  = 821) from two centres, Ireland ( n  = 546) and the USA ( n  = 275), was performed. This included 290 RTRs with KC and 444 without. Eleven single nucleotide polymorphisms (SNPs) in the MTHFR gene and seven in the overlap gene MTHFR Chloride transport protein 6 ( CLCN6) were evaluated and association explored by time to event analysis (from transplant to first KC) using Cox proportional hazards model. Results: Polymorphism at MTHFR CLCN6 (rs9651118) was significantly associated with KC in RTRs (HR 1.50, 95% CI 1.17–1.91, p  < 0.00061) and cSCC (HR 1.63, 95% CI 1.14–2.34, p  = 0.007). A separate SNP, MTHFR C677T, was also significantly associated with KC in the Irish population (HR 1.31, 95% CI 1.05–1.63, p  = 0.016), but not American RTRs. Conclusions: We report the association of a SNP in the MTHFR overlap gene, CLCN6 and KC in a combined RTR population. While the exact function of CLCN6 is not known, it is proposed to be involved in folate availability. Future applications could include incorporation in a polygenic risk score for KC in RTRs to help identify those at increased risk beyond traditional risk factor assessment. Abstract : Time from date of transplant to development of keratinocyte skin cancer (Irish cohort n  = 500) CLCN6 . CC (usual) allele is solid line and heterozygous or homozygous variants for the MTHFR CLCN6 (rs9651118) polymorphism are indicated here by the broken lines.